Estudio de Factibilidad para la creación de un Centro de Capacitación y Nivelación dirigida a la Población entre las edades de 10 a 19 años del Cantón Chinchipe, Provincia de Zamora Chinchipe. - Guevara Villacís., Blanca Cecilia (2016)
The thesis entitled FEASIBILITY STUDY FOR CREATING A LEVEL TRAINING CENTER AND DIRECTED TO THE POPULATION AGES 10 TO 19 YEARS OF Chinchipe Canton, province of Zamora Chinchipe; made to comply with the prerequisite for the degree of Engineer in Banking and Finance, of the National University of Loja. The following tube research objectives: Conduct a feasibility study for the creation of a training center and leveling aimed at the population between the ages of 10-19 years of the Canton Chinchipe, Zamora Chinchipe "; one that aims to give specialized classes through training and remedial education to improve the educational level of young chinchipences. The specific objectives are proposed: 1) Conduct a market study in which it is determined: demand, per-capita use, unmet demand, supply, price analysis, analysis of advertising by applying computational tools; 2) Conduct a technical study (size, capacity, capacity utilization, location, project engineering, serving to identify the macro and microlocalization by tabulation matrix points to identify the exact place for project implementation; 3) Develop a organizational study - Administrative: Legal basis of constitution, organization, vision, mission and values; constitution has been made based on the laws and regulations in force Chinchipe Canton; and 4) Run a financial study; applying the tools of financial evaluation as net present value, internal rate of return, benefit-cost ratio, payback period of capital, sensitivity analysis. As a result of the application of those tools the value of the initial investment at $20,280.08, consisting of fixed assets with a value of $12,170.80, $3,384.00 deferred and current with a value of $4,725.26 was determined. In addition, the projected income and costs and income statements and cash flow was established. Where it was determined that the investment for the next project is $20,280.08, financed in equal parts: Finally, conclusions and recommendations to make decisions and adjustments necessary for the implementation of the project, among which stands out the most important are listed by the three partners; the company has a net present value of $25,728.76 US dollars, an internal rate of return of 52.90%; benefit-cost ratio of $1.34. And a recommendation informs prospective investors that this project is very profitable, therefore it must run considering the results of the application of each indicator showing that the project has a very low investment with good returns becoming a great opportunity for the entrepreneur. Within the methodology used in the application main form of 331 surveys the population 10 years of age a 19 Canton Chinchipe, still relevant in the selection of useful information for the project.